Conocimiento sobre métodos de planificación familiar en adolescentes abortivas que acuden al servicio de hospitalización de ginecología del Hospital Regional Isidro Ayora de la ciudad de Loja - González Solórzano, Patricia Karina (2014)
Adolescence brings biological, psychological and psychosocial changes, the emergence of new needs and capabilities. Teen pregnancy has occurred since ancient times of humanity and some of them were unwanted. This type of pregnancy for certain authors have no designation of timely and arise in present times for sex without or with inadequate contraceptive use, which is associated with lack of information or ignorance. These pregnancies occur in women, adolescents at higher rates. This research seeks to determine the knowledge about family planning in the abortion adolescents presenting to inpatient gynecology Regional Hospital Isidro Ayora city of Loja. The type of study was quantitative, transversal and descriptive. The methodology included a structured survey. Conclusion: 15% have a good degree of knowledge, 16.67% have a degree of knowledge about regular contraception and the level of knowledge about family planning in the 68.33% is bad. The most common age of abortion is both belonging to the age group of 15-19 years. The most common cause that induces abortion in adolescents is the lack of family support 41.67%. The family planning method most commonly used in this population is emergency contraception 50% method. Keys: Adolescence, abortion, family planning, contraception